2021
DOI: 10.1016/j.ejmp.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Monte Carlo calculated dose enhancement ratios for gold nanoparticles irradiated by X-rays: Assessing the uncertainty and correct methodology for extended beams

Abstract: Results of a Monte Carlo code intercomparison exercise for simulations of the dose enhancement from a gold nanoparticle (GNP) irradiated by X-rays have been recently reported. To highlight potential differences between codes, the dose enhancement ratios (DERs) were shown for the narrow-beam geometry used in the simulations, which leads to values significantly higher than unity over distances in the order of several tens of micrometers from the GNP surface. As it has come to our attention that the figures in ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…The above findings (specifically at 6 MV) might find confirmation and some understanding in terms of the recent literature on in silico studies, [46][47][48] as refers to 15 nm AuNPs, with the distinction that the observed DEF values are in line with the available literature, but they were obtained at lower AuNPs concentrations. Future work in our new kV breast RT project will show if higher concentrations in vivo produce significantly higher DEF and SER values at MV as well as kV photon energies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The above findings (specifically at 6 MV) might find confirmation and some understanding in terms of the recent literature on in silico studies, [46][47][48] as refers to 15 nm AuNPs, with the distinction that the observed DEF values are in line with the available literature, but they were obtained at lower AuNPs concentrations. Future work in our new kV breast RT project will show if higher concentrations in vivo produce significantly higher DEF and SER values at MV as well as kV photon energies.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, our still‐ and time‐resolved cell microscopy observations point toward a very significant presence of AuNPs clustering in cellular vesicles, where AuNPs clusters form and disrupt with a time scale in the order of tens of seconds: an effect which deserves further investigation on the radio‐sensitization efficiency and possible shielding of low‐energy secondary electrons, for a given AuNPs concentration in the cell culture medium. 48 …”
Section: Discussionmentioning
confidence: 99%
“…energy range contribute negligibly to the total energy transported out of the GNP (see supplementary Fig. S1), but are relevant for the local dose increase in the proximity of the GNP ( Rabus et al 2021b).…”
Section: Internal Consistency Of Simulation Resultsmentioning
confidence: 99%
“…First results from the exercise have been reported by Li et al ( 2020aLi et al ( , 2020b and the relation of the DER values with those relevant for realistic irradiation scenarios with extended photon beams have been discussed by Rabus et al ( 2019Rabus et al ( , 2021b. This work focusses on the methodology used in the assessment of the reported results for consistency between the different cases (GNP sizes, X-ray spectra) and for consistency with the principle of energy conservation.…”
Section: /13mentioning
confidence: 99%
“…Other important aspects of the localized energy deposition at the nanometer scale around the NP and their biological consequences have been recently summarized in H. Rabus et al [ 28 ]. In this paper, it is shown that the calculated DEF corresponds to a ~10 ionization in the immediate vicinity of the GNP.…”
Section: Discussionmentioning
confidence: 99%